Communication for social behaviour change: the use of games and posters to promote sanitation and hygiene practices (2014)
People receive health information from a variety of sources and their health status depends, largely on whether they can understand and remember the health information they receive. Current communication strategies are failing in this regard. Most people forget what their educators tell them and others remember the information incorrectly (Anderson JL, Dodman S, Kopelman M, Fleming A, 1979 and Kessels, 2003). Hence, health services researchers have tested many different types of interventions to improve people's understanding of health information, change health behaviours, and improve health outcomes. However, only a limited number of these interventions have been studied to determine their efficacy, especially among people with low health literacy (DeWalt, 2006). Improved communication between health educators and the people will be a great benefit especially for low literate people within the community. Therefore, there is the need to improve the ability of health educators to convey health information to low literate population to improve their knowledge of essential health information. Hence, the development of effective communication strategies to improve the knowledge of low health literate population will also benefit more literate populations (Dower, Knox, Lindler and O'Neil, 2006). Studies indicate that community health workers are a cost effective way to improve people's access to health knowledge and health-related behaviours (Lam, McPhee, Mock, et al. 2003). Trained health educators are para-professionals specifically trained to work with people to increase their knowledge about health promotion and to improve their overall health conditions. If people know they need to understand certain health information, they can reduce the confusion and miscommunication that currently exists (Elder, Ayala and Campbell, et al, 2006; Sherrill, Crew, Mayo, Mayo, Rogers and Haynes, 2005) hence, the need for effective communication strategy in behaviour change communication for promoting positive health behaviour towards social development.